2013
DOI: 10.1021/ol402032a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Anti-Markovnikov Hydroalkylation of Homoallylic Alcohols Bearing β-Fluorines

Abstract: A palladium-catalyzed anti-Markovnikov hydroalkylation of β,β-difluorinated homoallylic alcohols with alkylzinc reagents has been developed. This method affords a wide range of synthetically useful gem-difluorinated compounds with good functional group compatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…11 (F) Zhang and co-workers directly coupled 3,3,3-bromodifluoro-1-propene to arylboronic acids with high regioselectivity (α-substitution) and chemoselectivity (aldehydes were unreacted under the reaction conditions). 12 (G) Ichikawa and co-workers found conditions for a selective γ-attack (S N 2′) of 3,3,3-bromodifluoro-1-propene by 1,2-bromoheteroarenes to give 3,3-difluoroallylic compounds which could undergo an intramolecular radical cyclisation to gain access to 3-difluoromethylated dihydrobenzoheteroles.…”
Section: Spotlight Syn Lettmentioning
confidence: 99%
See 1 more Smart Citation
“…11 (F) Zhang and co-workers directly coupled 3,3,3-bromodifluoro-1-propene to arylboronic acids with high regioselectivity (α-substitution) and chemoselectivity (aldehydes were unreacted under the reaction conditions). 12 (G) Ichikawa and co-workers found conditions for a selective γ-attack (S N 2′) of 3,3,3-bromodifluoro-1-propene by 1,2-bromoheteroarenes to give 3,3-difluoroallylic compounds which could undergo an intramolecular radical cyclisation to gain access to 3-difluoromethylated dihydrobenzoheteroles.…”
Section: Spotlight Syn Lettmentioning
confidence: 99%
“…(E) Lin and Qing showed that the difluorohomoallylic alcohols and amines (prepared from the reactions shown above) could undergo an anti-Markovnikov hydroalkylation in the presence of an organozincate under palladium catalysis with an oxidant (benzoquinone under an air atmosphere). 11 (F) Zhang and co-workers directly coupled 3,3,3-bromodifluoro-1propene to arylboronic acids with high regioselectivity (α-substitution) and chemoselectivity (aldehydes were unreacted under the reaction conditions). 12 (G) Ichikawa and co-workers found conditions for a selective γ-attack (S N 2′) of 3,3,3-bromodifluoro-1-propene by 1,2-bromoheteroarenes to give 3,3-difluoroallylic compounds which could undergo an intramolecular radical cyclisation to gain access to 3-difluoromethylated dihydrobenzoheteroles.…”
Section: Brmentioning
confidence: 99%
“…19 F NMR (282 MHz, CDCl 3 ): δ = -108.3 (dt, J = 246.6, 10.5 Hz, 1 F), -110.4 (dt, J = 246.6, 10.5 Hz, 1 F). (2,2-Difluoro-1-hydroxybut-3-en-1-yl)benzoate (3b) 27 Yield: 220 mg (91%); white crystals; mp 53-54 °C.…”
mentioning
confidence: 99%
“…2,2-Difluoro-1-(furan-2-yl)but-3-en-1-ol (3n) 30 Yield: 155 mg (89%); yellow oil. 2,2-Difluoro-1-(thien-2-yl)but-3-en-1-ol (3o) 27 Yield: 150 mg (79%); yellow oil. R f = 0.33 (hexanes/EtOAc, 5:1).…”
mentioning
confidence: 99%